Surface Roughness of Composite Resins Subjected to Hydrochloric Acid - Roque,Ana Carolina Cabral (2015)
The purpose of this study was to determine the influence of hydrochloric acid on surface roughness of composite resins subjected to brushing. Sixty samples measuring 2 mm thick x 6 mm diameter were prepared and used as experimental units. The study presented a 3x2 factorial design, in which the factors were composite resin (n=20), at 3 levels: microhybrid composite (Z100), nanofilled composite (FiltekTM Supreme), nanohybrid composite (Ice), and acid challenge (n=10) at 2 levels: absence and presence. Acid challenge was performed by immersion of specimens in hydrochloric acid (pH 1.2) for 1 min, 4 times per day for 7 days. The specimens not subjected to acid challenge were stored in 15 mL of artificial saliva at 37 oC. Afterwards, all specimens were submitted to abrasive challenge by a brushing cycle performed with a 200 g weight at a speed of 356 rpm, totaling 17.8 cycles. Surface roughness measurements (Ra) were performed and analyzed by ANOVA and Tukey test (p≤0.05). Surface roughness values were higher in the presence (1.07±0.24) as compared with the absence of hydrochloric acid (0.72±0.04). Surface roughness values were higher for microhybrid (1.01±0.27) compared with nanofilled (0.68 ±0.09) and nanohybrid (0.48±0.15) composites when the specimens were not subjects to acid challenge. In the presence of hydrochloric acid, microhybrid (1.26±0.28) and nanofilled (1.18±0,30) composites presents higher surface roughness values compared with nanohybrid (0.77±0.15). The hydrochloric acid affected the surface roughness of composite resin subjected to brushing.